Answer:
y = -1x + 7
Step-by-step explanation:
y2 - y1 / x2 - x1
9 - 0 / -2 - 7
9 / -9
= -1
y = -1x + b
0 = -1(7) + b
0 = -7 + b
7 = b
hiiksbsjxbxjsoahwjsissnsks
Answer:
I think the answer is D.
Step-by-step explanation:
Well, if you look at the last few sentences in that picture, it says that "he earns money depending how long he babysits." It's a clue to the answer, so the answer is obviously D.
I am also sorry if my answer is wrong. It might be c but please comment on my answer if you disagree/think it's wrong.
Answer:
c
Step-by-step explanation: